Modeling Cross-Cultural Interaction in Ancient Borderlands - Costion, Kirk E.; Green, Ulrike Matthies (Book collections on Project MUSE., 2018)
This book introduces the Cross Cultural Interaction Model (CCIM) as a tool to visually display and organize the inherent complexity of the social, economic, and political interactions that take place in multicultural borderlands or across long distances.